Existence of Equilibria and Fixed Points of Set-Valued Mappings on Epi-Lipschitz Sets with Weak Tangential Conditions. (24th February 2016) - Bounkhel, Messaoud
Abstract : We prove a new result of existence of equilibria for an u.s.c. set-valued mapping F on a compact set S of R n which is epi-Lipschitz and satisfies a weak tangential condition. Equivalently this provides existence of fixed points of the set-valued mapping x ⇉ F ( x ) - x . The main point of our result lies in the fact that we do not impose the usual tangential condition in terms of the Clarke tangent cone. Illustrative examples are stated showing the importance of our results and that the existence of such equilibria does not need necessarily such usual tangential condition.